Everything in place: peace and harmony in an overcrowded home. (November 2019) - Errázuriz, Tomás
Discourses on storage and clutter have become central issues in contemporary domestic space. The anxiety caused by accumulation and disorder are directly related to the progressive entry of goods into homes. Now, what happens in the case of some elderly homeowners whose lifestyles have changed little over the past decades and have a much different relationship to current consumer culture and domestic accumulation? Based on an auto-ethnographic approach, this visual essay looks at the home the author's grandparents have built throughout their life. It argues that, although the house is full of objects that have been accumulating over the decades, these objects can hardly be catalogued as stuff. Material and symbolic stability are favoured by the reduced traffic of objects entering and leaving the house and the importance of care and maintenance practices but, overall, by the ability of the house to provide a specific and differentiated place for each object.